Frequency and nature of pain following single visit root canal treatment (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The purpose of this study was to compare the frequency and nature of pain between the vital inflamed (n=55) and non-vital (n=55) teeth that received single visit root canal treatment. The frequency and nature of pain were assessed as no pain, mild, moderate and severe pain on day 2 and day 7. The results showed that 76.4 and 85.5% participants felt no pain in vital inflamed teeth on day 2 and day 7, respectively. On the other hand, 63.6 and 74.5% participants felt no pain in non-vital teeth on day 2 and day 7, respectively. The remaining participants only felt mild to moderate pain. There were no significant difference between the two groups (p=0.435 on day 2 and p=0.371 on day 7). The results suggested that single visit root canal treatment is equally effective in both vital inflamed and non-vital teeth.